Dynamic Response of a Floating Dual Vertical-Axis Tidal Turbine System with Taut and Catenary Mooring Under Extreme Environmental Conditions in Non-Operating Mode - Yunjun Lee; Jinsoon Park; Woo Chul Chung (Journal of Marine Science and Engineering, 2025)
This study analyzes the dynamic response of a floating dual vertical-axis tidal turbine platform under extreme environmental loads, focusing on two different mooring systems as follows: taut and catenary. The analysis assumes a non-operational turbine state where power generation is stopped, and the vertical turbines are lifted for structural protection. Using time-domain simulations via OrcaFlex 11.4, the floating platform’s motion and mooring line effective tensions are evaluated under high waves, strong wind, and current loads. The results reveal that sway and heave motions are significantly influenced by wave excitation, with the catenary system exhibiting larger responses due to mooring system features, while the taut system experiences higher mooring effective tension but shows more restrained motion. Notably, in the roll direction, both systems exhibit peak frequencies unrelated to the wave spectrum, attributed instead to resonance with the system’s natural frequencies—0.12438 Hz for taut and 0.07332 Hz for catenary. Additionally, the failure scenario of ML02 (Mooring Line 02) and the application of dynamic power cables to the floating platform are analyzed. The results demonstrate that under non-operational and extreme load conditions, mooring system type plays a main role in determining platform stability and structural safety. This comparative analysis offers valuable insights for selecting and designing mooring configurations optimized for reliability in extreme environmental conditions.